Extended Release Liposomal Bupivacaine Injection (Exparel) for Early Postoperative Pain Control Following Pharyngoplasty. Issue 3 (May 2018) - Day, Kristopher M.; Nair, Narayanan M.; Griner, Devan; Sargent, Larry A.
Abstract : Background: Liposomal bupivacaine (LB, Exparel) is a long-acting local anesthetic reported to decrease postoperative. The authors demonstrate the first safe use of LB in pediatric patients with improved pain control following pharyngoplasty. Methods: Retrospective case-control of all the patients who underwent pharyngoplasty at a tertiary craniofacial center from March 2010 to June 2016. Treatment group (TG) administered 1.3% LB and 0.5% bupivacaine and 1:200, 000 epinephrine. Control group (CG) administered 0.5% lidocaine with 1:200, 000 epinephrine. Pain scores, oral intake, opioids administered, and duration of hospitalization were measured. Results: Sixty patients (30 males, 30 females; average age 6.2 ± 2.4 years, weight 20.9 ± 6.8 kg) were evenly divided into a TG that received 3.5 ± 2.1 mL (2.6 ± 1.9 mg/kg) LB and 2.0 ± 2.3 mL 0.5% bupivacaine and a CG that received 2.7 ± 3.2 mL lidocaine. Treatment group patients had lower initial face, legs, activity, cry, consolability pain scale scores (0.1 ± 0.55/10, P = 0.0049; CG 4.5 ± 1.1/10, P = 0.00061) and no significant inpatient pain score difference 0 to 36 hours postoperative ( P = 0.32–0.53). Oral intake was tolerated 0.21 ± 0.12 days ( P < 0.0001) earlier by the TG and with greater first 24-hour average volume (377.6 ± 351.9 cc, P < 0.0001). Treatment group patients were discharged 1.8 ± 0.87 days ( P = 0.00023) earlier and required lower average opioids (15.1 ± 11.2 mg hydrocodone-equivalents) than CG (27.5 ± 19.1 mg hydrocodone-equivalents; P = 0.0017). Conclusions: Liposomal bupivacaine is safe in pediatric patients, associated with less opioids, increased and earlier oral intake, and shorter hospital stay.